Senses of Sense - Pickstock, Catherine (NTT, 2019)
Recent years emphasis on contemplation, prayer and ritual has raised new questions about the site of theological reflection: is an inhabited theology newly disclosive? What are the implications of such an appreciation of the role of the body of language, gesture, posture, sound, variations of light and space, the passage of time for theological understanding? The space of the liturgy, the edifice of the Church or the performed space of enactment becomes a dramatization and exteriorisation of the mind, of unfallen reason which remembers that it is created and is now at one with the diversity of creation and with God, where knowing and unknowing coincide in illumination and the forgetting of the self.